Courage the cowardly dog. Season four [videorecording (DVD)] - Dilworth, John R., 1963- (Cartoon Network hall of fame., 2016)
For a sleepy little outpost like Nowhere, Kansas, chaos and catastrophe have no trouble finding Courage and his crusty owners, Muriel and Eustace. In this season's episodes, Courage must face a diseased alien species and a pregnant squid, rescue Muriel from a cunning duck and a love-sick swamp monster, calm a jealous mansion bent on destroying their farmhouse, and more. Sometimes Courage must even save his little family from themselves!